Effects of Teaching Lexical Bundles on EFL Students’ Abstract Genre Academic Writing Skills Improvement: Corpus-Based Research Design - Birhan, Amare Tesfie (Universitas Negeri Makassar, 2021)
Lexical bundles are two or more string of words that co-occur frequently in a corpus. Hence, this corpus-based research design study examines the effects of lexical bundles on English as a foreign language learner’s abstract genre academic writing skills, and it also investigates students’ perception towards lexical bundles instruction to enhance their academic writing skills. Hence, frequent lexical bundles were selected from 70 computer science articles. These articles were selected from 7 journals that were published in reputable, indexed, and through representative criteria. Accordingly, sixteen frequent lexical bundles were selected through corpus analysis software (Laurence Anthony’s Antconc software) for the purpose of classroom instruction. The bundles are intended to help computer science students to develop their abstract genre academic writing skills. Students have instructed their academic writing through corpus informed instruction for two months, and the data were gathered through pre and post-tests and questionnaire. The findings indicated that lexical bundles have a positive effect on students’ academic writing skills, particularly abstract genre writing. Besides, the students have a positive perception of the lexical bundle and the instruction to enhance their academic writing skills. Finally, this research calls attention to discipline-oriented lexical bundles since they are crucial for academic writing.